1989
DOI: 10.1116/1.584438
|View full text |Cite
|
Sign up to set email alerts
|

Polymer deposition and etching mechanisms in C2F6 radio-frequency plasma as studied by laser-induced fluorescence

Abstract: Spatial profiles of CF2 concentration in C2 F6 rf plasma are measured by the laser-induced fluorescence method. The observed profiles are explained by the generation and recombination reaction mechanisms of CF2 . It is found that the deposition rate of fluorocarbon polymer on SiO2 film is proportional to [CF2]n ; n=2.5–3.0, whereas the etch rate of SiO2 is proportional to [CF2]. Both the etching and the deposition reactions proceed at the same time. Based on these observations, reaction mechanisms for fluoroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Kitamura et al 19 reported that the rate was proportional to 2.5 to third power of the CF 2 partial pressure. Accordingly, it is certain that the rate of R 3 is not linearly dependent on the CF x partial pressure, unlike in the case of R 1 .…”
Section: Resultsmentioning
confidence: 98%
“…Kitamura et al 19 reported that the rate was proportional to 2.5 to third power of the CF 2 partial pressure. Accordingly, it is certain that the rate of R 3 is not linearly dependent on the CF x partial pressure, unlike in the case of R 1 .…”
Section: Resultsmentioning
confidence: 98%
“…Polymer layers on the surface are easily formed in fluorocarbon discharges with high concentrations of radical species, like CF, CF 2 , and CF 3 . [10][11][12] However, generally these radicals themselves do not contribute to the polymer film formation. Contrariwise, in many cases a net radical flux from the surface into the plasma glow has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…5 The CF 2 radical is an important species in halocarbon plasmas because it influences the balance between polymer deposition and etching, and hence selectivity, in silicon/silicon dioxide etching applications. 1,2 As a result, a number of previous experimental studies have reported 1D measurements of CF 2 density using mass spectrometry, 6 infrared diode laser-absorption, [7][8][9][10] and laser-induced fluorescence, [11][12][13][14][15][16][17][18][19] but, to our knowledge, the present results are the first complete 2D measurements of CF 2 density in any reactor. In addition to yielding information on the relative magnitude of CF 2 concentration at various conditions, these measurements are of interest because they provide insight into the plasma uniformity through 2D visualization of the CF 2 spatial distribution.…”
Section: Introductionmentioning
confidence: 72%